CHI3L1 enhances melanoma lung metastasis via regulation of T cell co-stimulators and CTLA-4/B7 axis - Ma, Bing; Kamle, Suchitra; Akosman, Bedia; Khan, Hina; Lee, Chang-Min; Lee, Chun Geun; Elias, Jack A. (Frontiers in Immunology, 2022)
ICOS/ICOSL and CD28/B7-1/B7-2 are T cell co-stimulators and CTLA-4 is an immune checkpoint inhibitor that play critical roles in the pathogenesis of neoplasia. Chitinase 3-like-1 (CHI3L1) is induced in many cancers where it portends a poor prognosis and contributes to tumor metastasis. Here we demonstrate that CHI3L1 inhibits the expression of ICOS, ICOSL and CD28 while stimulating CTLA-4 and the B7 moieties in melanoma lung metastasis. We also demonstrate that RIG-like helicase innate immune activation augments T cell co-stimulation, inhibits CTLA-4 and suppresses pulmonary metastasis. At least additive antitumor responses were seen in melanoma lung metastasis treated with anti-CTLA-4 and anti-CHI3L1 antibodies in combination. Synergistic cytotoxic T cell-induced tumor cell death and the heightened induction of the tumor suppressor PTEN were seen in co-cultures of T and tumor cells treated with bispecific antibodies that target both CHI3L1 and CTLA-4. Thus, CHI3L1 contributes to pulmonary metastasis by inhibiting T cell co-stimulation and stimulating CTLA-4. The simultaneous targeting of CHI3L1 and the CTLA-4 axis with individual and, more powerfully with bispecific antibodies, represent promising therapeutic strategies for pulmonary metastasis.